Sensibility in the era of global communication. A semioethic perspective - Petrilli, Susan (Signs - International Journal of Semiotics, 2007)
This paper proposes a phenomenological and semiotic analysis of sensibility, or feeling, in the era of globalization which is the era of global communication: how are such things as time, space, self, others, life, death, health, illness, work, employment, unemployment, free-time, development, underdevelopment, etc., perceived in today’s world? As vast as this excursion may seem, these different issues are relative to dominant sensibility today and can all be conducted to the problem of the relation between identity and alterity. The hypothesis is that the common denominator in science and sensibility today is the ideology, or ideo-logic, of identity. However, with reference to Europe, for example, the ideo-logic of identity is also a menace to the difficult process of forming the European Union. In Europe, indeed in world history at large, the logic of identity and of alterity can both be traced in all the most important phases that have determined the destiny of the people in history. In the current phase of development in the social reproduction system, that of advanced capitalism, the contrast between identity and alterity is at an extreme, at the point of exasperation. In this paper we also intend to explore the possibility of opening sensibility to alterity not only in Europe, but in the anthroposociosemiosic sphere at large.